Occupational health nurses’ contribution to health care workers’ health - Bigaignon-Cantineau, Janine; Gonzalez, Maria; Broessel, Nathalie; Denu, Brigitte; Hamzaoui, Halim; Cantineau, Alain (SJWEH Supplements, 2005)
' ' OBJECTIVES ': 'Data are unavailable concerning legislation and the roles and activities of occupational health nurses in relation to health care workers. This survey was undertaken to identify these aspects of occupational health nurses and collect data on the topic in various countries. ' ' METHODS ': 'A questionnaire was sent to prominent professionals in European countries and then to professionals in other countries. ' ' RESULTS ': 'The study confirmed that very little is known about the number of occupational health nurses in this field. Training varies, but the more training they have, the more diversified their activities are. ' ' CONCLUSIONS ': 'This survey emphasizes the need to develop training and education for occupational health nurses so that they can efficiently help occupational health physicians and contribute towards assessing occupational risks among occupational health care workers, particularly in light of the lack of trained occupational health physicians.
Keywords: activity; education; health; health care worker; legislation; nurse; occupational health nurse; risk assessment; training; worker